Toxic Masculinity and Compulsive Heteronormativity in Konkona Sen’s Movie, A Death in the Gunj - Ranjitkar, Palistha (Khwopa Journal, 2023)
Gender is one of the most contested subjects in literature. Some prominent scholars like Judith Butler have argued that gender is not innate, but performative. For instance, masculinity is a construct which is always believed to resonate with a compulsive heteronormativity. The fact that men have to behave like an actual “macho; the giver ; the doer completely contrasting feminine virtues such as the emotional , passive and the receiver is prescriptive of the ways through which heteronormativity has become naturalized since the beginning of the civilization. This paper looks into the subtle details about the rooted construct of heteronormativity resembled in the movie “A death in the Gunj’(2016) . Here the protagonist Shutu faces spiritual conflict between his naturally innate virtues like kindness, sensitivity, introversion which goes quite contrary to the compartmentalized masculine virtues such as assertiveness, bravery, manhood and a pressure to maintain a proper “macho” personality. This research looks into the prominent crisis of masculinity and gender performativity that the world faces today. Is it only essential to venerate the so called masculine virtues like dominance and assertiveness? If yes , what about kindness, sensitivity and the capacity to feel emotions that are so much sidelined as feminine virtues? What is the position of man in the modern society? The movie “ A death in Gunj “ paradoxically opens up these hard questions through the characterization of Shuttu who remains unloved and forsaken and drives himself towards the annals of self-destruction and suicide for the reason that he finds himself very vaguely suited to fit into the societal constructs of what makes a proper “man’. This research employs Judith Butler’s concept of gender performativity to look into all these prominent gender questions. It also employs Lacan’s construct of symbolic order where language is a source of both alienation and subjectivity considering the fact that while language structures our understanding of self and reality, it alienates from the self that stemmed from the imaginary order from our authentic selves.